2019
DOI: 10.1002/mp.13955
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating human and learned domain knowledge into training deep neural networks: A differentiable dose‐volume histogram and adversarial inspired framework for generating Pareto optimal dose distributions in radiation therapy

Abstract: Purpose We propose a novel domain‐specific loss, which is a differentiable loss function based on the dose‐volume histogram (DVH), and combine it with an adversarial loss for the training of deep neural networks. In this study, we trained a neural network for generating Pareto optimal dose distributions, and evaluate the effects of the domain‐specific loss on the model performance. Methods In this study, three loss functions — mean squared error (MSE) loss, DVH loss, and adversarial (ADV) loss — were used to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 79 publications
1
60
0
Order By: Relevance
“…When we compared our results with these previous results, we found that the average absolute dose differences of most evaluation metrics in the structure-based model were smaller than those of Nguyen et al by using the GAN (Table 4). Some papers demonstrated that the prediction of the GAN outperformed the U-net based architecture [5,11], and this tendency was also seen in the present study (Table 4). Moreover, an extremely small deviation was observed in both prediction models and the prediction performance was comparable to the previous results even when the CT images were used for the training (Table 4).…”
Section: Plos Onesupporting
confidence: 87%
See 2 more Smart Citations
“…When we compared our results with these previous results, we found that the average absolute dose differences of most evaluation metrics in the structure-based model were smaller than those of Nguyen et al by using the GAN (Table 4). Some papers demonstrated that the prediction of the GAN outperformed the U-net based architecture [5,11], and this tendency was also seen in the present study (Table 4). Moreover, an extremely small deviation was observed in both prediction models and the prediction performance was comparable to the previous results even when the CT images were used for the training (Table 4).…”
Section: Plos Onesupporting
confidence: 87%
“…In the fairly recent past, researchers have begun to use of deep neural networks (DNN) to predict the dose distribution, engendering a new field of research [4][5][6][7][8][9][10][11][12]. Such dose prediction is useful for confirming the achievable dose distribution before or during the creation of treatment planning, and could reduce the iterative optimization process for IMRT, because the treatment planner can know which areas should receive increased or reduced doses based on the results of the prediction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that deep learning models that use anatomical structures and static beam orientations to predict Pareto optimal dose distributions could generate multiple optimal plans with differing trade-offs in real time. 44,55 However, Pareto optimal dose predictions for IMRT prostate plans with variable beam numbers and orientations have not yet been studied. In this paper, we present an approach that uses deep learning networks to predict Pareto optimal dose distributions for prostate IMRT plans that involve anatomical structures and varying beam numbers and orientations.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with Pareto optimal dose prediction models, which can generate multiple plans that have differing trade‐offs between the different critical structures. Previous studies found that deep learning models that use anatomical structures and static beam orientations to predict Pareto optimal dose distributions could generate multiple optimal plans with differing trade‐offs in real time 44,55 . However, Pareto optimal dose predictions for IMRT prostate plans with variable beam numbers and orientations have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%